2022
DOI: 10.3389/fmicb.2022.857720
|View full text |Cite
|
Sign up to set email alerts
|

Potential Probiotic Strains From Milk and Water Kefir Grains in Singapore—Use for Defense Against Enteric Bacterial Pathogens

Abstract: Kefir grains consist of complex symbiotic mixtures of bacteria and yeasts, and are reported to impart numerous health-boosting properties to milk and water kefir beverages. The objective of this work was to investigate the microbial communities in kefir grains, and explore the possibility of deriving useful probiotic strains from them. A total of 158 microbial strains, representing six fungal and 17 bacterial species, were isolated from milk and water kefir grains collected from a Singapore-based homebrewer. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 82 publications
0
25
0
Order By: Relevance
“…Our results showed that Bacillus had better growth curve, bile salt, and trypsin tolerance, while Lactobacillus had good acid tolerance ability. For further detecting the ability to bind epithelial cell sites of isolates, in the present study, porcine intestinal epithelial cells (IPEC-J2) and the method was used as previous study described [ 27 , 53 ]. The BA40 showed the strong ability to outcompete pathogens for epithelial cell adhesion sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that Bacillus had better growth curve, bile salt, and trypsin tolerance, while Lactobacillus had good acid tolerance ability. For further detecting the ability to bind epithelial cell sites of isolates, in the present study, porcine intestinal epithelial cells (IPEC-J2) and the method was used as previous study described [ 27 , 53 ]. The BA40 showed the strong ability to outcompete pathogens for epithelial cell adhesion sites.…”
Section: Discussionmentioning
confidence: 99%
“…We used agar well diffusion to test antimicrobial activity of isolates from JinHua pigs [ 27 , 28 ]. Briefly, the broth (LB or RCM) with 1.5% agar (10 mL) was poured onto the sterile Petri plates (10 × 10 mm).…”
Section: Methodsmentioning
confidence: 99%
“…Zymomonas as fermenting agents of plant saps is commonly used to produce alcoholic beverages. Often isolated from milk and kefir grains, Zymomonas strains may exhibit various probiotic properties (Azeredo et al, 2010;Tan et al, 2022;Tallyne de Aguiar Silva et al, 2020) including inhibition of pathogenic microorganisms (Weir, 2016) and explain some health benefits provided by fermented foods to consumers (Marco et al, 2017;Rul et al, 2022). Nevertheless, research is actively needed to sustain and achieve the probiotic potentials of this genera.…”
mentioning
confidence: 99%
“…The health-promoting properties of kefir are likely attributable to its unique microbiota profile. The primary bacterial and fungal genera in kefir include lactobacilli, Lactococcus, Streptococcus, Leuconostoc, Acetobacter, Saccharomyces, Kluyveromyces, and Candida [21], [169]. Several species isolated from kefir have been found to exhibit probiotic properties.…”
Section: Kefir Benefits and Microbial Compositionmentioning
confidence: 99%
“…Prebiotic characteristics of hydrolysed polysaccharides were then evaluated, such as the capacity to resist digestion by acidic pH and digestive enzymes typical of the human GIT. The selective substrate utilisation assay was next conducted to determine if derived polysaccharides could be selectively utilised by beneficial probiotics, specifically kefir-derived probiotics [169], but were not utilised by, or could inhibit, the growth of pathogens. Polysaccharides which demonstrated prebiotic efficacies were combined with kefir probiotics (Chapter 3) and tested in an ex-vivo model which simulates the large bowel to determine their effects on gut microbial communities and SCFA content.…”
Section: Introductionmentioning
confidence: 99%